2022
DOI: 10.5937/inovacije2203120z
|View full text |Cite
|
Sign up to set email alerts
|

Classes supported by digital technologies: The application of the blog as a virtual tool in biology teaching

Abstract: Innovations in technology are rapid and workers' roles in the virtual environment have changed. Due to the great need to educate professionals who need to adapt quickly, the modernization of teaching is gaining momentum. Blog is one of the internet tools that can be effectively implemented in education. The aim of the research is to experimentally test the effects of the application of the blog Biosoikoslogos in biology teaching in relation to traditional teaching and to evaluate the attitudes of first-grade h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 36 publications
0
1
0
Order By: Relevance
“…The reason for choosing this direction of research was the observation that students perceive physics as an interesting but difficult and work-intensive subject (Angell et al, 2004) and the existence of various difficulties in understanding many concepts (Şahin & Yağbasan, 2012). On the other hand, numerous studies have shown that innovative teaching approaches contribute to increasing student performance (Lazarević et al, 2018;Maričić et al, 2020;Skinner et al, 2017;Taylor et al, 2014;Županec et al, 2022). Also, it was stated that visualization plays an important role as an effective tool in the teaching process (Dori et al, 2007;Vavra et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…The reason for choosing this direction of research was the observation that students perceive physics as an interesting but difficult and work-intensive subject (Angell et al, 2004) and the existence of various difficulties in understanding many concepts (Şahin & Yağbasan, 2012). On the other hand, numerous studies have shown that innovative teaching approaches contribute to increasing student performance (Lazarević et al, 2018;Maričić et al, 2020;Skinner et al, 2017;Taylor et al, 2014;Županec et al, 2022). Also, it was stated that visualization plays an important role as an effective tool in the teaching process (Dori et al, 2007;Vavra et al, 2011).…”
Section: Discussionmentioning
confidence: 99%